PENGARUH PENGUKURAN BALANCE SCORECARD TERHADAP KINERJA PERUSAHAAN (STUDI KASUS PT. INDO VENEER UTAMA) - Ema Mustika Saputri; Indra Lila Kusuma; Iin Emy Prastiwi (ITB AAS INDONESIA, 2021)
This research was aimed to influence of financial perspectives, customer perspectives, internal business perspectives, growth and learning perspectives on company performance. PT. Indo Veneer Utama. The analysis used an independent variable of ompany performance and the independent perspectives of finance, customers, internal business, and growth and learning. The sample of this reseach are work es on PT. Indo Veneer Utama.The sample was canducted by random sampling method. Callecting data was to 82 questionnaires. The results of this study indicate that financial perspectives, customer perspectives, internal business perspectives have a significant effect, while growth and learning perspectives have a significant effect on company performance. Keywords : Financial Perspective, Customer Perspective, Internal Business Perspective, Learning and Growth Perspective, Company Performance.